Can the gut be the missing piece in uncovering PD pathogenesis?. (February 2019) - Chapelet, Guillaume; Leclair-Visonneau, Laurène; Clairembault, Thomas; Neunlist, Michel; Derkinderen, Pascal
Abstract: It is now well established that Parkinson's disease (PD) is not only a movement disorder of the CNS but also a gastrointestinal disorder affecting the enteric nervous system (ENS). The gut-brain axis is a bidirectional communication between the brain and the gastrointestinal tract, which comprises besides the CNS and the ENS, the intestinal epithelial barrier, the intestinal microbiota and the enteroendocrine systems. In this review, we present the clinical and pathological evidence suggesting that the gut-brain axis is dysfunctional in PD by discussing the possible role of gut microbiota, inflammation and permeability in the development of the disease.